Study on Electron Tunneling in Microtubules: A Model Explaining Both Mendelian Genetics and Quantum Computing Memory - George Pieczenik; Srul David Pieczenik (New Frontiers in Medicine and Medical Research Vol. 17, 2021)
The model for microtubule tunneling also predicts the independent and random assortment of Mendelian genes as explained by the Boveri-Sutton hypothesis. Electron tunneling from the centriole to the kinetochore is the driving electro chemistry for chromosomes to move at the same velocity. Microtubules have been proposed to act as quantum computational molecules. They have also been proposed to act as discrete on-off bit computation molecules. The model of the microtubule can be understood with both contexts of computation.